2012
DOI: 10.4038/sljog.v34i2.4825
|View full text |Cite
|
Sign up to set email alerts
|

Serum magnesium levels in preterm labour

Abstract: Introduction: Preterm infants are at a greater risk of short term and long term complications including disabilities and impediments in growth and mental development. Hence, to predict and prevent the occurrence of preterm labour and delivery would go a long way to reduce the morbidity and mortality resulting from it. Preterm labour followed by preterm delivery is a major issue in India. Besides various etiologies, preterm labour may be due to a biochemical alteration, such as magnesium. Many recent findings h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In their study, Bhat and Waheed evaluated the relationship between socio-economic class and preterm labor and found a significant association between low socio-economic class and preterm labor (P < 0.05) (31). They also found a significant difference in serum magnesium level between 3 groups of high, medium, and low socio-economic classes.…”
Section: Discussionmentioning
confidence: 91%
“…In their study, Bhat and Waheed evaluated the relationship between socio-economic class and preterm labor and found a significant association between low socio-economic class and preterm labor (P < 0.05) (31). They also found a significant difference in serum magnesium level between 3 groups of high, medium, and low socio-economic classes.…”
Section: Discussionmentioning
confidence: 91%
“…Numerous new studies have highlighted the importance of magnesium in human biology. 11 There is proof that changes and alterations in magnesium metabolism have an undesirable effect on pregnancy and its outcome. Another study 15 showed that women with preterm labor have proportionally low serum magnesium levels (60%) compared to women having normal labor (32%).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous new studies have highlighted the importance of magnesium in human biology. 11 There is proof that changes and alterations in magnesium metabolism have an undesirable effect on pregnancy and its outcome.…”
Section: Discussionmentioning
confidence: 99%